Mifepristone Repurposing in Treatment of High-Grade Gliomas - Llaguno-Munive, Monserrat; Vazquez-Lopez, Maria Ines; Jurado, Rafael; Garcia-Lopez, Patricia (Frontiers in Oncology, 2021)
Glioma is the most common and aggressive primary tumor of the central nervous system. The standard treatment for malignant gliomas is surgery followed by chemoradiotherapy. Unfortunately, this treatment has not produced an adequate patient response, resulting in a median survival time of 12-15 months and a 5-year overall survival of <5%. Although new strategies have been sought to enhance patient response, no significant increase in the global survival of glioma patients has been achieved. The option of developing new drugs implies a long and costly process, making drug repurposing a more practical alternative for improving glioma treatment. In the last few years, researchers seeking more effective cancer therapy have pursued the possibility of using anti-hormonal agents, such as mifepristone. The latter drug, an antagonist for progesterone and glucocorticoid receptors, has several attractive features: anti-tumor activity, low cytotoxicity to healthy cells, and modulation of the chemosensitivity of several cancer cell lines in vitro. Hence, the addition of mifepristone to temozolomide-based glioblastoma chemotherapy may lead to a better patient response. The mechanisms by which mifepristone enhances glioma treatment are not yet known. The current review aims to discuss the potential role of mifepristone as an adjuvant drug for the treatment of high-grade gliomas.